PROMOTING CHARACTER EDUCATION IN EFL CLASSROOM: USING CHILDREN’S LITERATURE AS A TEACHING MATERIAL - Mentari Antika Putri; Sri Harto; Nicke Yunita Moecharam (Journal of English and Education, 2017)
The article entitled Promoting Character Education in EFL Classroom: Using Children’s Literature as Teaching Material investigated a teacher’s strategies in integrating character education in EFL classroom using children’s literature as teaching material along with teacher’s ability to identify the ideology embodied in the story. A case study was employed in this study. The basic frameworks of this study are relied on Campoy (1997), Edgington (2002), O’sullivan (2004) and Hollindale (1988) framework. This study revealed that the teacher employed several strategies namely Cause/Effect/Far-Reaching Effect, Perspective Windows, What’s Your Perspective?, Comparison of Noble and Ignoble Character, Value Inculcation and Value Analysis. It is further found that teacher was able to identify the ideology presented in the story.